THE USE OF DEICTIC EXPRESSIONS IN STUDENTS’ ORAL PRESENTATION - Endang Yuliani Rahayu (Dinamika Bahasa dan Budaya, 2018)
The current study explored the use of deictic expressions by the first semester students of English Letters, FBIB UNISBANK in their oral presentations of Performative Spoken English. Included in the deictic expressions are those of  personal pronouns, time, place and discourse. Note taking was used to collect the data from the total population during oral presentation in PSE (performative Spoken English) classes. The data were purely analyzed qualitatively without any numeric calculation.  Errors made by the students  were then analyzed employing Richards’ Error Classification Criteria (https://www.professorjackrichards.com/ ). The findings indicate that all types of deictic expressions were used except that at discourse level.  At first it was assumed that the students failed to observe gthe rules of deictic expressions. But, after Focus Group Discussion (FGD), it also turned out that some students actually only made errors in the use of deictic expressions. The students  managed to identify the errors and to correct them It is therefore recommended that more practice be done on the part of the students.Key words: deictic expressions, oral presentation, error analysis, focus group discussion